Memórias de mulheres: livro-reportagem com perfis biográficos de femininos múltiplos - Almeida, Dielen dos Reis Borges (2015)
This paper reports the process to produce the non-fiction book Women\'s Memories: biographical profiles of multiple feminine. It begins with the following problem: how the female protagonism is constructed throughout history? It presents as epistemological reference the historical materialism and as the theoretical reference the British cultural studies. It adopts gender as a category of analysis and reviews the literature about feminism and women\'s history, especially in relation to education, communication and technology. The methodology includes techniques of oral history to research the memories of sources and literary journalism to write the book. Four women with different characteristics and life trajectories are interviewed: Zélia, 54 years old, victim of various forms of violence who held herself and her daughters through hard manual work; Bruna, 20 years old, student and feminist activist of the Slut Walk; Beatriz, 62 years old, teacher who is scared about the retirement, which chose not to marry or have children and keeps dating for 32 years; Carol, 31 years old, who was adopted as a child, priestess who worships the Goddess and the sacred feminine. The narrative of the four profiles is permeated by a fifth self-reflexive narrative of the author. It concludes that the protagonism of women is built through a multiple feminine.